2021
DOI: 10.1002/pol.20210745
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐friendly solution processing of all‐polymer solar cells: Recent advances and future perspective

Abstract: All-polymer solar cells (all-PSCs) exhibit great potentials in commercial applications. All-PSCs have observed steady performance gains with power conversion efficiency now reaching over 17% in the open literature. However, the current processing of all-PSCs relies predominantly on toxic, chlorinated solvents in moisture-free environments, representing a significant barrier for their commercialization due to the added costs to handle and dispose of such solvents. There is thus an urgent need for safe, environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 106 publications
(111 reference statements)
0
10
0
Order By: Relevance
“…Generally, the non-halogenated solvents, such as toluene, ortho-xylene (o-XY), and 1,2,4-trimethylbenzene, have high boiling points, which lead to long film-drying time and large phase separation. [35,40] It has been demonstrated that hot slotdie coating is an effective method to suppress the excessive phase separation of non-halogenated solvents processed active layers. [22,41,42] However, the high-solution temperature of hot slot-die coating will reduce the pre-aggregation of polymer donors, leading to the decrease of crystallinity, which is bad for thick-film devices.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the non-halogenated solvents, such as toluene, ortho-xylene (o-XY), and 1,2,4-trimethylbenzene, have high boiling points, which lead to long film-drying time and large phase separation. [35,40] It has been demonstrated that hot slotdie coating is an effective method to suppress the excessive phase separation of non-halogenated solvents processed active layers. [22,41,42] However, the high-solution temperature of hot slot-die coating will reduce the pre-aggregation of polymer donors, leading to the decrease of crystallinity, which is bad for thick-film devices.…”
Section: Introductionmentioning
confidence: 99%
“…It offers excellent solvation of photoactive materials, thus making it a relatively viable and safer choice to replace chlorobenzene and CF in OPVs. , Furthermore, its relatively high boiling point also makes it suitable for R2R-compatible meniscus-guided thin-film printing processes. 2-MeTHF has also previously been employed in OPVs to replace halogenated processing solvents. It can be derived from sustainable and renewable furfural biomass (i.e., corn stover, rice straw, etc. ). Its eco-friendly synthesis makes it an excellent choice for reactions involving organometallics, organocatalysis, biotransformations, and so forth. , Considering the sustainable and eco-friendly nature of 2-MeTHF, it was employed in this work to process photoactive layer.…”
Section: Resultsmentioning
confidence: 99%
“…The OFETs were characterized in a nitrogen-filled glove box using a semiconductor characterization system (Keithley 4200-SCS). The PSCs were fabricated with a conventional device architecture of glass/indium tin oxide (ITO)/MoO 3 /polymer:PC 71 BM/Ca/ Al [48,49]. The ITO was cleaned via sonication in deionized water, acetone, and isopropanol, followed by UV-ozone treatment for 15 min.…”
Section: Fabrication Of Field-effect Transistors and Photovoltaic Dev...mentioning
confidence: 99%